(untitled) (Baghdad Science Journal, 2007)
A new mixed ligand complexes have been prepared between 8- hydroxy quinoline and o-hydroxybenzylidene-1-phenyl-2,3-dimethyl-4-amino-3-pyrazolin-5-on with Mn(II),Fe(II),Co(II),Ni(II) and Cu(II) ions . the prepared complexes were isolated and characterized by (FT-IR)and (UV-Vis) spectroscopy. Elemental analysis (C.H.N) Flame atomic absorption technique . in addition to magnetic susceptibility and conductivity measurement.